SAT0104 Treatment with methotrexate in rheumatoid arthritis patients on stable biological treatment gives better outcomes over time. (12th June 2018) - Boone, N.; Sepriano, A.; Janknegt, R.; van derKuy, H.; Peeters, R.; Landewé, R.
Abstract : Background: In patients with rheumatoid arthritis (RA) biological-Disease Modifying Anti-Rheumatic Drugs (bDMARDs) should be used preferentially in combination with methotrexate (MTX) as prescribed by EULAR [1] . The longitudinal treatment-effect of combination treatment compared to bDMARD monotherapy in daily clinical practice is not yet well known. Objectives: To test in a registry of patients with RA the longitudinal effect of combination therapy (i.e. MTX and bDMARDs) compared to monotherapy (i.e. bDMARDs only) on the likelihood to be in clinical remission over time. Methods: Adult RA patients on stable treatment with conventional synthetic disease modifying drugs (csDMARDs) and/or biologic DMARDs (bDMARDs) were followed in one centre. During clinical visits every 3 months up to 3 years rheumatologists/research nurses collected clinical- and medication data. The effect of a (time-varying) combination treatment strategy (i.e. MTX and bDMARDs) as compared to monotherapy with bDMARDs on the likelihood to be on DAS28 (≤2.6) and RAPID3 (0-30) (≤3) remission was tested in longitudinal binomial generalized estimating equations (GEE) models (one model per outcome). In addition, the effect of combination therapy compared to monotherapy on each individual component of DAS28 [tender joint count (TJC; 0-28); swollen joint count (SJC; 0-28); patient global assessment (PGA; 0-10) and ESR (mm/h)] was tested in separate longitudinal linear GEE models. All models were adjusted for possible confounders selected 'a priori' on clinical grounds: age, gender, drugs for comorbidities (yes/no), oral steroids (yes/no) and NSAID (yes/no). Results: A total of 330 patients were included [mean (SD) age: 62 (12) years, 68% female, baseline mean (SD) DAS28: 3.3 (1.4) and RAPID3: 11.5 (6)]. The mean (SD) follow-up period and disease duration were 10.7 (9.7) months and 11.2 (9.6) years respectively. Combination treatment was significantly associated with a 55% higher likelihood to be in DAS28-remission (but not RAPID3-remission) over time compared with bDMARDs monotherapy (table 1). In addition, combination treatment resulted in a decrease on the SJC over time as compared to monotherapy [β=-0.91 (95% CI: -1.77; -0.06)]. No significant differences between the two treatment strategies were seen for the other DAS28 components. Conclusions: These results give support to the recommendation that continuing MTX in patients with RA under biological therapy increases the likelihood of clinical remission (especially when assessed with objective measures) and thus should be encouraged. Reference: [1] Smolen JS, et al. Ann Rheum Dis 2014;73:492-509. Disclosure of Interest: None declared